Rhamnetin decreases the expression of HMG-CoA reductase gene and increases LDL receptor in HepG2 cells - Raghad R. Al-Yousef; Manal M. Abbas; Razan Obeidat; Manal A. Abbas (GarVal Editorial Ltda., 2023)
Context: Rhamnetin is a naturally occurring methylated derivative of quercetin. This flavonoid is abundant in Syzygium aromaticum, Coriandrum sativum Prunus cerasus, and Rhamnus spp. Aims: To evaluate the effects of rhamnetin on HMG-CoA reductase and low-density lipoprotein receptor (LDLR) gene and protein expressions in the HepG2 hepatoma cell line. Methods: The expression of HMG-CoA reductase and LDLR genes and proteins were studied in HepG2 liver cancer cell line by PCR, Western blot, and indirect ELISA, as well as their antioxidant activity. Results: Rhamnetin was non-toxic up to 200 μM on HepG2 at 24, 48, and 72 h. Rhamnetin (25 µM) upregulated LDLR gene expression by 1.66 folds compared to 3.12 folds exerted by the well-known hypocholesterolemic drug simvastatin. Rhamnetin (100 µM) increased the expression of LDLR protein at the cell membrane, while the other concentrations produced no significant change from the control (vehicle-treated). In HepG2 cell lysate, LDLR was increased by 50 µM of rhamnetin. Also, rhamnetin increased SOD activity significantly by 100.98, 86.28, and 100.98% by the concentrations 25, 50, and 100 µM, respectively. Using the same concentrations, rhamnetin reduced H2O2 levels by 50, 67, and 76.34%, respectively. Conclusions: This study demonstrated for the first time that rhamnetin reduced HMG-CoA reductase gene expression and increased LDLR in HepG2 cells.